2022
DOI: 10.3390/ijerph19031634
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Support for Pregnant Women Provided by English Stop Smoking Services and National Health Service Trusts: A Survey

Abstract: Reducing smoking rates in pregnancy continues to be a public health priority. Given a recent UK government policy change resulting in The National Health Service (NHS) making a significant new contribution to cessation support in pregnancy in England, in addition to that of Local Authorities (LA), an up-to-date assessment of national support offered to pregnant women is needed. LA Stop Smoking Service (SSS) managers and representatives from maternity services in NHS Trusts were invited to participate in an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…The smoking cessation rate observed in our study is nearly one-third (33.9%) of the rates reported in previous studies 22–24 . One likely explanation could be the stricter inclusion criteria for pre-pregnancy smokers in our study; we included only the women who were regular smokers 3 months before knowing they were pregnant.…”
Section: Discussionmentioning
confidence: 74%
“…The smoking cessation rate observed in our study is nearly one-third (33.9%) of the rates reported in previous studies 22–24 . One likely explanation could be the stricter inclusion criteria for pre-pregnancy smokers in our study; we included only the women who were regular smokers 3 months before knowing they were pregnant.…”
Section: Discussionmentioning
confidence: 74%
“…Three surveys of English NHS Stop Smoking Services (NHS SSS) found that nearly all services which responded provided behavioural support and nicotine replacement therapy (NRT) [31–33]. Other interventions were rarely provided; only 14% reported using incentives and 11% reported using e‐cigarettes [33].…”
Section: Methodsmentioning
confidence: 99%
“…Defining, costing and estimating the quit rate of usual care for smoking cessation in pregnancy Three surveys of English NHS Stop Smoking Services (NHS SSS) found that nearly all services which responded provided behavioural support and nicotine replacement therapy (NRT) [31][32][33]. Other interventions were rarely provided; only 14% reported using incentives and 11% reported using e-cigarettes [33]. These were excluded from our definition of usual care.…”
Section: Defining the Cohortmentioning
confidence: 99%
“…Other studies suggest that barriers to access exist, including time constraints (e.g. because of childcare and work responsibilities) [ 16 ], a ‘postcode lottery’ in service availability and quality [ 16 , 18 ], finding services inflexible in terms of the treatment options offered [ 16 , 19 ], and fear of judgement by healthcare professionals [ 16 , 20 , 21 ]. In the UK, the NHS Long Term Plan smokefree pregnancy pathway [ 22 ] has recently been introduced to provide a more integrated system of maternity-led support, though it is unclear whether this will meet the support needs of those who find it hard or do not want to engage with standard interpersonal support as most barriers remain.…”
Section: Introductionmentioning
confidence: 99%